The value of CA125 in predicting adverse outcomes in heart failure patients - Hao, Phan Thai (Edelweiss Applied Science and Technology, 2025)
In heart failure, elevated carbohydrate antigen 125 (CA125) has been shown to correlate with adverse events. We sought to quantify its prognostic usefulness in predicting the one-month combined death/heart failure readmission endpoint. Carbohydrate antigen 125 (CA 125), originally associated with ovarian cancer, has now garnered attention as a potential marker for fluid overload and pulmonary congestion in heart failure patients. However, determining the optimal CA 125 cutoff value for predicting one-month adverse outcomes in heart failure patients remains an area of variability across different research studies. While both biomarkers show promise, further research is needed to determine their comparative utility in predicting adverse outcomes in heart failure patients. Factors such as sensitivity, specificity, and optimal thresholds should be considered. Study objectives: determine the prevalence of in-hospital or one-month mortality and one-month readmission in heart failure patients; determine the cutoff point, AUC, sensitivity, and specificity of CA 125 in predicting in-hospital or one-month mortality and one-month readmission in heart failure patients. Our cross-sectional study enrolled 121 heart failure patients at the HCMC Hospital of Rehabilitation - Occupational Diseases during the period from September 1, 2023, to July 1, 2024. During the one-month follow-up period, there were 6 cases lost to follow-up, accounting for 6/121=4.95%. The mean age was 69.14 ± 12.96 years, with men comprising 51.2% of the cohort. The median CA 125 value was 29.28 U/mL (interquartile range: 22.57–37.24). There were 2 cases accounting for 1.7% of in-hospital mortality. There were 8 cases, accounting for 6.6%, who died one month after discharge from the hospital. There were 30 cases, accounting for 24.8%, of re-hospitalization within one month of discharge. The optimal CA 125 cutoff for predicting in-hospital mortality was > 91.6 U/mL, yielding an AUC ROC of 0.885 (95% CI: 0.812–0.937, p < 0.0001), sensitivity of 100%, and specificity of 85.8%. The optimal CA 125 cutoff for predicting one-month mortality was > 29.6 U/mL, yielding an AUC ROC of 0.667 (95% CI: 0.573–0.752, p = 0.120), sensitivity of 87.5%, and specificity of 53.3%. The optimal CA 125 cutoff for predicting one-month rehospitalization was ≤44.3 U/mL, yielding an AUC ROC of 0.508 (95% CI: 0.413–0.602, p = 0.889), sensitivity of 80%, and specificity of 35.3%. The optimal CA 125 cutoff for predicting the one-month combined endpoint of death/rehospitalization was > 26.05 U/mL, yielding an AUC ROC of 0.534 (95% CI: 0.438–0.627, p = 0.543), sensitivity of 66.67%, and specificity of 51.32%. CA 125 demonstrates good accuracy in predicting in-hospital mortality with a cutoff of > 91.6 U/mL, an AUC ROC of 0.885 (95% CI: 0.812–0.937, p < 0.0001), sensitivity of 100%, and specificity of 85.8%.